Body proportions and environmental adaptation in gorillas. Issue 3 (27th November 2021) - Ruff, Christopher B.; Junno, Juho‐Antti; Burgess, M. Loring; Canington, Stephanie L.; Harper, Christine; Mudakikwa, Antoine; McFarlin, Shannon C.
Abstract: Objectives: Limb length and trunk proportions are determined in a large, taxonomically and environmentally diverse sample of gorillas and related to variation in locomotion, climate, altitude, and diet. Materials and methods: The sample includes 299 gorilla skeletons, 115 of which are infants and juveniles, distributed between western lowland ( G. gorilla gorilla ), low and high elevation grauer ( G. beringei graueri ), and Virunga mountain gorillas ( G. b. beringei ). Limb bone and vertebral column lengths scaled to body mass are compared between subgroups by age group. Results: All G. beringei have relatively short 3rd metapodials and manual proximal phalanges compared to G. gorilla, and this difference is apparent in infancy. All G. beringei also have shortened total limb lengths relative to either body mass or vertebral column length, although patterns of variation in individual skeletal elements are more complex, and infants do not display the same patterns as adults. Mountain gorillas have relatively long clavicles, present in infancy, and a relatively long thoracic (but not lumbosacral) vertebral column. Discussion: A variety of environmental factors likely contributed to observed patterns of morphological variation among extant gorillas. We interpret the short hand and foot bones of all G. beringei as genetic adaptations to greater terrestriality in the last common ancestor of G. beringei ; variation in other limb lengths to climatic adaptation, both genetic and developmental; and the larger thorax of G. b. beringei to adaptation to reduced oxygen pressure at high altitudes, again as a product of both genetic differences and environmental influences during development.